Program SMART-EAT (Strategi Makan Remaja Terpadu melalui Edukasi Asupan Terpenuhi) untuk Peningkatan Pola Makan Sehat Remaja: The SMART-EAT (Integrated Adolescence Eating Strategy trough Fulfilled Intake Education) Program to Improve Healthy Eating Patterns for Youth - Rifa, Nisrina Nailah; Yulistianingsih, Ari; Malik, Tiara Aoliyana; Aulia, Anaya Zahra; Auliani, Nauli (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Adolescence is an important period in the human life cycle and a crucial phase in the formation of eating patterns that have a long-term impact on nutritional status. The SMART-EAT (Integrated Adolescence Eating Strategy through Fulfilled Intake Education) program was implemented to increase awareness of and promote healthy eating habits among grade XII students at MA Mafatihul Huda, Cirebon. This activity includes a survey of student numbers, calculating nutritional needs, planning a balanced lunch menu, measuring nutritional status, providing lunch, and evaluating food acceptance. Based on the nutritional status measurement, 40% of students were underweight, 30% were normal, 16.67% were overweight, and 13% were obese. The lunch menu prepared contained 929 kcal, 33.4 g of protein, 40 g of fat, and 123.1 g of carbohydrates, which were within the range of students' daily lunch needs. The acceptability evaluation showed that 90% of the 30 students liked the food served, although actual consumption was not optimal. This program demonstrates that a nutritious lunch intervention can be a strategic step toward improving adolescent diets and supporting better nutritional status.